Q: What does k plus f plus s plus t plus f plus f equals g of an ES?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

=b+2h+r+x+z+q+a+p+l+f+g+d

gf(5) = g(f(5)) = g(5+1) since f(x) = x+1 and then g(6) = 3*6 - 2 = 18 - 2 = 16

578392g

No, they are not equivalent.

=2969726895655+g+f+k+x

Related questions

f(x)=x+1 g(f(x))=x f(x)-1=x g(x)=x-1

No, by itself it is not.

g(x) = 5. So whatever f(x) or f(-1) is, g of that is going to be 5.

g(x) = x + 3 Then f o g (x) = f(g(x)) = f(x + 3) = sqrt[(x+3) + 2] = sqrt(x + 5)

Let f ( x ) = 3 x 5 and g ( x ) = 3 x 2 4 x

=b+2h+r+x+z+q+a+p+l+f+g+d

x = 75

gf(5) = g(f(5)) = g(5+1) since f(x) = x+1 and then g(6) = 3*6 - 2 = 18 - 2 = 16

f = 54

8 equals fingers on the human hand (plus 2 thumbs)

578392g

f and g are inverse functions.